Effect of wine barrel ageing or sapa addition on total polyphenol content and antioxidant activities of some Italian craft beers. (17th September 2014) - Sanna, Vanna; Pretti, Luca
Summary Beer is a complex mixture of bioactive polyphenols with positive health effects, and its composition is influenced by some technological variables. In this study, the total polyphenol content (TPC) and the antioxidant activity of some Italian craft beers produced by ageing in wood barrel that previously contained red or white wines, and by addition of sapa, a cooked must from wine grapes, were investigated. TPC greatly vary among different beer types. Craft beers stored in wood barrels that contained red wines, such as those added of sapa from red wine grapes, showed a TPC up to 2.5 times higher (1000 GAE mg L−1) compared with other craft beers, and 3.6 times higher than the industrial beer. The antioxidant activity is remarkably different depending on beer type and strictly correlated with TPC. Results indicate that antioxidant properties of the craft beers could be efficiently improved by the explored technological processes.